Clinical examination for hyperlinear palms to determine filaggrin genotype: A diagnostic test accuracy study. Issue 11 (18th October 2021) - Bradshaw, Lucy E.; Haines, Rachel H.; Thomas, Kim S.; Chalmers, Joanne R.; Irvine, Alan D.; Williams, Hywel C.; Brown, Sara J.
Abstract: Background: Palmar hyperlinearity is a feature of ichthyosis vulgaris, the monogenic skin disorder caused by FLG loss‐of‐function mutations. Objective: To investigate how well the presence or absence of hyperlinear palms (HLP) detect FLG genotype in children. Methods: STARD criteria are used to report this diagnostic accuracy study. Phenotype and genotype data (four most prevalent FLG null mutations) were obtained from a total of 3656 children in three studies: the UK CLOTHES trial (children 1–5 years with moderate–severe atopic eczema); UK BEEP trial (2 year olds at high risk of developing atopic eczema); UK‐Irish eczema case collection (0–16 year olds with atopic eczema). All participants included in analyses of HLP as the index test and FLG genotype as the reference were of white European ancestry. Results: Thirty‐two percent of participants (1159/3656) had FLG null mutation(s) and 37% (1347/3656) had HLP. In 13% (464/3656), HLP was recorded as 'unsure' or not recorded. The sensitivity and specificity of HLP for detecting FLG mutations in each of the studies was: 67% (95% CI 55–78%) and 75% (67–82%) in CLOTHES; 46% (36–55%) and 89% (86–91%) in BEEP; 72% (68–75%) and 60% (57–62%) in the UK‐Irish case collection. Positive and negative likelihood ratios were: 2.73 (1.95–3.81) and 0.44 (0.31–0.62) in CLOTHES; 4.02 (2.99–5.40) and 0.61 (0.52–0.73) in BEEP; 1.79 (1.66–1.93) and 0.47 (0.42–0.53) in the UK‐Irish collection. Discussion: Trained observers were able to define palmar hyperlinearity in the majority (3191/3656, 87%) of cases. The presence of HLP is not a reliable sign to detect FLG mutations, but the absence of HLP excludes FLG null genotype with a reasonable degree of certainty. Abstract : Palmar hyperlinearity is associated with FLG loss‐of‐function mutations. This diagnostic test accuracy study used data previously collected as part of three paediatric cohorts, including a total of 3656 children. We aimed to investigate whether the presence or absence of hyperlinear palms (HLP) could be used to detect FLG genotype in children. Thirty‐two percent of participants (1159/3656) had FLG null mutation(s) and 37% (1347/3656) had HLP. The presence of HLP was not a reliable clinical sign for the detection of F LG mutations.